Answers

2014-11-09T12:26:57+05:30
T* t^{2} = t^{3}
 s^{2} *-s=-( s^{3} )
      
                                         hope i helped u friend
0
The Brainliest Answer!
  • Brainly User
2014-11-09T12:32:41+05:30
Answer:
   Rule :
           In Multiplication , when bases are same powers are added.

here base = t and powers of t are 1 and 2
               hence sum of powers of t =1+2 =3
       therefore ,  t×t²=


s²×(-s)= (-s)² × (-s) (because (- s)² = s²)

here base = -s
 powers of -s are 2 and 1
 sum of powers of -s = 1+2 =3
Apply rule , when bases are same powers are added .
therefore ,
     s²×(-s)= -s³

Hope This helps You!!
Thank You!!!

Cheers !!!


1 5 1